FRAUD PREVENTION: THE IMPACT OF INTERNAL CONTROLS AND AUDITOR PROFESSIONALISM - Astuti, Wati Aris (Faculty of Economics and Business, University of Pasundan, 2024)
Fraud is an illegal act committed by one or more individuals, either from within or outside an organization, intended to provide personal or group benefits while causing harm to others. This article aims to examine the impact of internal control systems on fraud prevention and the role of internal auditor professionalism in mitigating fraud within state-owned enterprises (BUMN) in Bandung. The research employs a descriptive verification method using primary data collected via questionnaires distributed directly to state-owned enterprises in Bandung. Hypotheses were tested using SPSS version 20 for data analysis. The study’s findings indicate that the implementation of internal control systems significantly affects fraud prevention, and the professionalism of internal auditors also plays a significant role in mitigating fraud in state-owned enterprises in Bandung.